Transforming Gender Role in Manjushree Thapa’s Seasons of Flight - Bhandari, Nagendra Bahadur (The Outlook: Journal of English Studies, 2022)
This article examines the transformation of gender identity of Prema, an immigrant girl from a mountainous village of Nepal to the metropolis of the US in Manjushree Thapa’s Seasons of Flight. The novel synchronizes the spatial journey of this village girl with her mental and emotional transformation. In course of her journey, she persistently crosses the cultural and social expectation for a girl born in typical Hindu family of the hinterland of Nepal. Particularly, she takes crucial decision of her life independently, supports her family financially and enjoys liberated sexual life. For this, she resists numerous social and cultural restrictions and obligations which gradually transform her as an independent girl. In this paper, Prema’s transformation process is analyzed through the critical frame of David Jefferess resistance model which emphasizes on transformation in perception, material reality and human relationship in resistance process.